The remodeling of glycoconjugates in mice - Hennet, Thierry; Ellies, Lesley G. (Biochimica et biophysica acta, 1999)
A role for glycoconjugates in mediating cellular interactions is well established. To further understand the formation, function and regulation of various glycoconjugates in vivo, gene targeting approaches have been applied to glycosyltransferase and glycosidase enzymes involved in different biosynthetic pathways. The growing number of gene targeted mice generated have brought confirmations of the importance of both core and terminal glycosylation enzymes in normal development and physiology. Of particular interest has been the degree of cell and tissue specificity of phenotypes generated by systemic null mutations as well as the number of enzymes belonging to multigene families having overlapping activities.